THE INFLUENCE OF HEALTH EDUCATION ON THE HANDS WASHING TECHNIQUE OF STUDENTS AT THE TAFSIR BOARDING SCHOOL, SURABAYA - PUTRI PAMUNGKAS (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2023)
Background: One of the best ways to prevent the spread of disease is to maintain good hand hygiene. In the Islamic boarding school environment, students often interact closely, so maintaining hand hygiene is important to prevent the spread of disease. Aim: this study was conducted to evaluate the effect of health education on the hand washing technique of students at Islamic boarding schools. Methods: This study used an experimental method with a pre-test and post-test control group design. The research sample consisted of 60 students, who were divided into two groups, namely the control group (30 people) and the intervention group (30 people). The intervention group was given health education about proper hand washing techniques, while the control group was not given health education. Data was collected by means of observation before and after the intervention using a checklist of correct hand washing techniques. The results of the study showed that after the health education intervention was carried out, there was a significant increase in students' hand washing techniques in the intervention group compared to the control group. In the intervention group, there was an increase in the percentage of correct hand washing technique from 50% before the intervention to 90% after the intervention, whereas in the control group, the percentage of correct hand washing technique only increased from 50% to 55%. Conclusion: It can be concluded that health education can influence students' hand washing techniques at Islamic boarding schools.